Hilda must be dancing - Wilson, Karma (Margaret K. McElderry Books, 2004)
Hilda Hippo tries other, quieter, activities when her jungle friends are disturbed by her dancing, but nothing else makes her happy until Water Buffalo suggests swimming and she finds a new way to express herself.